Stirred discs from polycaprolactone nanofibers highly doped with graphene for straightforward preconcentration of pollutants in environmental waters - Lhotská, Ivona; Háková, Martina; Erben, Jakub; Chvojka, Jiri; Švec, František; Šatínský, Dalibor (Talanta, 2024)
A novel sorbent for solid phase extraction (SPE) based on hybrid nanofibrous polycaprolactone containing graphene nanoparticles has been prepared. The preparation of hybrid polymer nanofibers with a very high 1:1 polymer/graphene ratio was achieved for the first time using alternating current electrospinning. The final appearance of these nanofibers was a thick porous layer that was cut into the shape of easy-to-handle extraction discs. Based on the preliminary study in which the graphene content varied, 30% graphene-doped nanofibers (w/w) exhibited the highest recoveries and enabled a significant increase in the retention of analytes, 2-25 times in comparison to PCL. The incorporation of graphene resulted in a higher surface area of 12 g/m2 compared to 2 g/m2 determined for the native polycaprolactone (PCL) nanofibers. This unique material was applied for a simple stirred disc sorptive extraction and preconcentration of trace levels of emerging organic environmental contaminants, bisphenols A, AF, AP, C, S, Z, 3-chlorophenol, and pesticides fenoxycarb, deltamethrin, and kadethrin from surface waters prior to HPLC-DAD determination. This was accomplished by stirring the unsupported nanofiber disc in a large-volume sample with RSD of five extractions of 3-15%. Recoveries yielded 87-120%, except 52% for bisphenol S due to its high polarity. Optimization of the extraction procedure included conditioning, sample volume, extraction time, and elution solvent. Our novel desorption procedure carried out in a vial used for the direct injection into the HPLC system significantly reduced sample handling and minimized potential human error.
Keywords: Disc; Environment pollutant; Nanofibers; Graphene; Sorptive extraction; Chromatography